2010
DOI: 10.1089/scd.2010.0009
|View full text |Cite
|
Sign up to set email alerts
|

Persistent High Glucose Concentrations Alter the Regenerative Potential of Mesenchymal Stem Cells

Abstract: Type 2 diabetes is associated with numerous long-term complications. This study aims to investigate whether impaired function of tissue-resident multipotent cells play role in pathogenesis of allied complications. Adipose-tissue-derived mesenchymal stem cells (ASCs) derived from nondiabetic (nASCs) and diabetic (dASCs) donors were compared with regard to glucose metabolism, cell replication, apoptosis, and differentiation potential. The data evidenced that elevation of glucose reduces proliferative capacity of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
139
3
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 189 publications
(150 citation statements)
references
References 40 publications
6
139
3
2
Order By: Relevance
“…Short-term expanded MSCs, as in the autologous setting, also elicit less innate immune attack when infused systemically, which supports their survival and function in vivo (24). There are reports of diabetesinduced changes in MSCs, including their regenerative potential, but these seem to mainly reflect effects of long-term hyperglycemia by, e.g., advanced glycation end products (25). In this study, we observed no defects in the expansion potential of MSCs after autologous harvest in subjects with recent-onset type 1 diabetes.…”
Section: Diabetesdiabetesjournalsorg Carlsson and Associatesmentioning
confidence: 85%
“…Short-term expanded MSCs, as in the autologous setting, also elicit less innate immune attack when infused systemically, which supports their survival and function in vivo (24). There are reports of diabetesinduced changes in MSCs, including their regenerative potential, but these seem to mainly reflect effects of long-term hyperglycemia by, e.g., advanced glycation end products (25). In this study, we observed no defects in the expansion potential of MSCs after autologous harvest in subjects with recent-onset type 1 diabetes.…”
Section: Diabetesdiabetesjournalsorg Carlsson and Associatesmentioning
confidence: 85%
“…30 In a rat diabetic model, MSC decreased osteogenic potential, 31 and exposure to high-glucose medium inhibited osteogenic differentiation and increased adipogenic differentiation in MG-63 osteosarcoma cells 32 and MSC. 33 Idei et al showed that the number of endothelial progenitor cells (EPC) and cell migration response to VEGF were significantly lower in atherosclerotic PAD patients compared to TAO patients, but the number and migration of EPC were similar between the TAO group and control group. 23 These results indicated that the functions of stem cells, including ATMSC, are compromised in diabetic patients.…”
Section: Discussionmentioning
confidence: 99%
“…1 H MR spectroscopy might be used to identify patients at risk for bone loss. Further studies are needed to osteoblastogenesis of stem cells while enhancing adipogenesis (29). These results suggest that insulin resistance leads to increased marrow fat formation and concordant inhibition of osteoblast formation.…”
Section: Musculoskeletal Imaging: Lipid Levels and Bone Marrow Fat Inmentioning
confidence: 91%